2012
DOI: 10.1248/bpb.b12-00726
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of a Human Intestinal Bacterium <i>Eggerthella</i> sp. CAT-1 Capable of Cleaving the C-Ring of (+)-Catechin and (−)-Epicatechin, Followed by <i>p</i>-Dehydroxylation of the B-Ring

Abstract: We isolated a human intestinal bacterium, capable of cleaving the C-ring and dehydroxylating the Bring of both ( )-catechin (2R,3S) and ( )-epicatechin (2R,3R). Although the strain was classified as Eggerthella (Eg.) lenta [named Eg. sp. CAT-1 (JF798636)] by 16S ribosomal RNA (rRNA) gene similarity, it was quite different in substrate specificity from a previously isolated strain, Eg. sp. SDG-2, which takes part in cleavage of the C-ring and dehydroxylation of the 3,4-dihydroxyphenyl moiety (B-ring) of (3R)-fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 14 publications
0
35
1
Order By: Relevance
“…So far, only a few bacterial species, some of them belonging to the class Clostridiales, such as Eubacterium sp. and Flavonifractor sp., and Eggerthella spp., have been reported to be able to initiate the metabolism of flavanol-3-ols (Jin & Hattori, 2012;Kutschera, Engst, Blaut, & Braune, 2011;Wang et al, 2001). Although batch incubations with fecal microbiota are limited by substrate depletion and the accumulation of the end products, they are appropriate for comparison of the microbial consequences of exposure to different sources or doses of compounds, such as the cranberry and grape seed extracts used in this study.…”
Section: Discussionmentioning
confidence: 99%
“…So far, only a few bacterial species, some of them belonging to the class Clostridiales, such as Eubacterium sp. and Flavonifractor sp., and Eggerthella spp., have been reported to be able to initiate the metabolism of flavanol-3-ols (Jin & Hattori, 2012;Kutschera, Engst, Blaut, & Braune, 2011;Wang et al, 2001). Although batch incubations with fecal microbiota are limited by substrate depletion and the accumulation of the end products, they are appropriate for comparison of the microbial consequences of exposure to different sources or doses of compounds, such as the cranberry and grape seed extracts used in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Available data have suggested a decrease of bifidobacteria population and increasing numbers of enterobacteria in the elderly , as well as a decrease in the levels of Lactobacillus, Eubacterium, and Bacteroides . Although it is not very clear which type of bacteria from the gut microflora is involved in the catabolism of flavonoids, some evidence suggests that Lactobacillus, Chlostridium, Eubacterium, and Bacteroides might be responsible for it . Recent work points out to Eggerthella lenta and F. Plauti as human intestinal bacteria responsible for the conversion of epicatechin to γ‐VL .…”
Section: Discussionmentioning
confidence: 99%
“…In the mechanism, degradation of the phloroglucinol ring is the inverse of the biosynthesis of the flavan-3-ol A ring, and it is closely related to the production metabolism of hydroxyphenyl-4-hydroxypentanoic acids (10 and 11) and 6 hydroxyphenyl-γ-valerolactones (12 and 13), which are major catechin metabolites produced by mammalian intestinal bacteria [6][7][8] and were not detected in this experiment. The metabolites 12 and 13 are produced by removal of 2 acetic acid units from 4 and 5 via intermediates 4a,b and 5a,b.…”
Section: Resultsmentioning
confidence: 81%
“…However, the bioavailability of tea catechins from the digestive tract is low [4,5]. Therefore, it has been suggested that catechin degradation products generated by intestinal bacteria are important in the biological activity of green tea [6][7][8]. Recently, we reported that Japanese postfermented tea produced by anaerobic microbial fermentation of green tea contained polyphenols identical to the tea catechin metabolites formed by mammalian intestinal bacteria [9].…”
Section: Introductionmentioning
confidence: 99%